AKIBAT HUKUM WANPRESTASI SERTA UPAYA HUKUM WANPRESTASI BERDASARKAN UNDANG-UNDANG YANG BERLAKU - Nur Azza Morlin Iwanti; Taun (The Juris, 2022)
In civil law, regarding agreements, the rights and obligations of the parties to the agreement have been regulated. The party giving the loan is called the creditor and the party receiving the loan is called the debtor. The creditor has the right to achieve, the debtor has the obligation to realize his achievements. However, in reality, the legal relationship between the two creditors and debtors, especially in terms of agreements, often encounters problems, resulting in default. Default itself is an event of failure in which a person does not comply with performance or failure to carry out obligations properly, causing loss to one of the parties concerned. This paper aims to explain what must be done in the event of default in an agreement.